A Note on Duopoly - Kristensen, Thorkil (Review of Economic Studies, 1938)
Journal Article A Note on Duopoly Get access Thorkil Kristensen Thorkil Kristensen Aarhus, Denmark Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 1, October 1938, Pages 56–59, https://doi.org/10.2307/2967538 Published: 01 October 1938